Tingkat Religiusitas Siswa (Studi Di SMA Negeri 1 Sangkulirang Kutai Timur) - Surono Surono; Mahfud Ifendi Mahfud (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Religiosity is a condition in an individual that encourages him to behave according to the level of his desire for religion. Thus, it is not impossible or very possible, that a person's religion or diversity will determine his attitude, not for students whose main task is learning. The higher understanding and knowledge of religion or religion will show a tendency to pay more attention to positive things. This article aims to measure the level of religiosity of students in SMA Negeri 1 Sangkulirang. The technique used to analyze the data in this study is a quantitative descriptive technique. This means that the average student religiosity of SMA Negeri 1 Sangkulirang is calculated through a frequency distribution table to determine the level/quality of each aspect of the dimension of student religiosity which includes the dimensions of ideology, ritual, practice, consequences, and intellectual dimensions. The results of the calculation of the average value of religiosity through the SPSS program, it is known that the lowest student religiosity value in SMA Negeri 1 Sangkulirang is 32.45, the highest value is 63.12, while the range of values ​​is 30.67. From the column of religiosity level, it is known that the average value is 49.999. After being consulted with the table of criteria for the level of religiosity, it appears that the average is in the interval of 47.79-55.44 with the